Inclusive Globalization and The Belt and Road Initiative - Jingyi Xie (UIN ALAUDDIN MAKASSAR, 2023)
The old economic globalization has come to a halt. Most scholars have considered the current model of economic globalization, and the new path of globalization is to inherit the parts of neoliberal economic globalization that benefit economic growth while reforming the parts that are insufficient. Many academics have backed China's